Diversidade sob o comando do capital: estudo de caso do NPD Orlando Vieira - Ferreira, Graziele Andrade (2021)
The present work presents the analysis of the case of the Orlando Vieira Digital Production Center (NPD), a project of the Municipality of Aracaju, linked to the Olhar Brasil Program of the Ministry of Culture (MinC), through the Audiovisual Secretariat (SAv), implemented, in 2016, in the government of President Luís Inácio Lula da Silva. The hypothesis developed is that the promotion of public cultural policies does not guarantee the democratic diversity of cultural production, considering the structural inequality of the current economic system. In this sense, implications of the adoption of policies for the protection of cultural diversity are presented, in a perimeter of public intervention in actions to promote independent audiovisual production, which allow the recognition of contradictions between the different levels of this policy model as a mechanism of resistance to trends of the cultural homogenization of globalization. The present investigation relates descriptive, qualitative, documentary and bibliographic research as a means for analytical work, theoretically anchored in the perspective of the Political Economy of Communication and Culture, in addition to contributions from studies on cultural diversity.